2019
DOI: 10.1007/978-3-030-26574-8_14
|View full text |Cite
|
Sign up to set email alerts
|

From COBOL to Business Rules—Extracting Business Rules from Legacy Code

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The functional requirements describe the performance of the current system. Software and hardware specifications required to construct a system are examples of non-functional requirements [11]. Use case diagrams are visual representations of the interactions between the system's actors developed by accounting for the system's use.…”
Section: Methodsmentioning
confidence: 99%
“…The functional requirements describe the performance of the current system. Software and hardware specifications required to construct a system are examples of non-functional requirements [11]. Use case diagrams are visual representations of the interactions between the system's actors developed by accounting for the system's use.…”
Section: Methodsmentioning
confidence: 99%
“…Many authors have worked on mining business rules from application code, namely: Sneed and Verhoef 25 focused on COBOL, Cosentino et al 26 on Java, Hnatkowska and Wazelinski 27 on C#, and Barbosa and Maia 28 or Mesbahi et al 29 on SQL procedures. Chittimalli et al 30 reported on a more ambitious goal: a language‐independent framework to extract the rules, 31 to create new ones, to verify them using the logs, and to analyze them.…”
Section: Related Workmentioning
confidence: 99%